Foreigners’ Rights in The Age of Pandemics – Migration Aspects - Princ, Marcin (University of Wroclaw. Faculty of Law, Administration & Economics, 2020)
The content of the article is devoted to the situation of foreigners – migrants – entering and staying in the territory of Poland. All considerations refer to the conditions of the pandemic. The author asks whether the introduced legal solutions are consistent with the rights and freedoms, and whether the restrictions are constitutional and, in particular, proportional to the threat. The subject of the analysis focuses mainly on Polish sources of law issued during the first wave of the epidemic in Poland. Many voices currently indicate that the pandemic situation in the global world could repeat itself in the future. Hence, the present experience should be used as a reference point in the future.
Keywords: cudzoziemcy; migranci; prawa człowieka; pandemie; prawa i wolności